2014
DOI: 10.1089/hum.2014.012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Adeno-Associated Virus Serotype and Tissue-Specific Expression on Circulating Biomarkers of Propionic Acidemia

Abstract: Propionic acidemia (PA) is an autosomal recessive inborn error of metabolism caused by deficiency of propionyl-CoA carboxylase (PCC). This enzyme is composed of six PCCA and six PCCB subunits and mediates a critical step in catabolism of odd chain fatty acids and certain amino acids. Current treatment options for PA are limited to stringent dietary restriction of protein consumption and some patients undergo elective liver transplantation. We previously generated a hypomorphic model of PA, designated Pcca

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 28 publications
(33 reference statements)
0
20
0
Order By: Relevance
“…The authors assume that gene therapy concurrently directed to hepatocytes and muscle cells would result in even better correction, as all tissues require PCC activity. They suggest that treatment of a wide array of tissues would represent the best option for PA disease correction . In a subsequent study, it was demonstrated that AAV‐mediated expression of Pcca resulted in long‐term phenotypic correction, although transgene expression decreased in the liver and in skeletal muscle.…”
Section: Therapy Targets and Treatment Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors assume that gene therapy concurrently directed to hepatocytes and muscle cells would result in even better correction, as all tissues require PCC activity. They suggest that treatment of a wide array of tissues would represent the best option for PA disease correction . In a subsequent study, it was demonstrated that AAV‐mediated expression of Pcca resulted in long‐term phenotypic correction, although transgene expression decreased in the liver and in skeletal muscle.…”
Section: Therapy Targets and Treatment Strategiesmentioning
confidence: 99%
“…It was demonstrated that adenovirus serotype 5 resulted only in a transient effect, whereas systemic administration of AAV serotype 8 resulted in more persistent correction of the biochemical phenotype . Next, the effectiveness of systemic therapy with AAV serotype 1 (muscle tropism), serotype 8 (liver tropism) and serotype rh10 (broad tropism) was studied and revealed that AAV serotype 8 in combination with a transthyretin promotor resulted in the most promising correction of the biochemical phenotype . The authors assume that gene therapy concurrently directed to hepatocytes and muscle cells would result in even better correction, as all tissues require PCC activity.…”
Section: Therapy Targets and Treatment Strategiesmentioning
confidence: 99%
“…This murine model survives into adulthood, while accurately recapitulating biochemical and clinical biomarkers similar to those in patients with PA. This highly useful model has been used to test Ad5 and different AAV vectors (muscle-biased AAV1, liver-biased AAV8 and broadly tropic AAVrh10) carrying a wild-type copy of the pccA gene to induce phenotypic correction [46,47]. Liver-targeted vectors mediated better correction than muscletargeted ones [47].…”
Section: Gene Therapymentioning
confidence: 99%
“…This highly useful model has been used to test Ad5 and different AAV vectors (muscle-biased AAV1, liver-biased AAV8 and broadly tropic AAVrh10) carrying a wild-type copy of the pccA gene to induce phenotypic correction [46,47]. Liver-targeted vectors mediated better correction than muscletargeted ones [47]. The effect, monitored as decrease in circulating diagnostic metabolites, is long-lasting, with sex-biased loss of expression of the transgene in liver and skeletal muscle, reducing the efficacy in females [48].…”
Section: Gene Therapymentioning
confidence: 99%
See 1 more Smart Citation